A novel strategy for fabricating biomimetic gradient metal-ceramic composites by dynamic freeze casting and pressure infiltration. (1st July 2019) - Yang, Li-Kai; Shen, Ping; Guo, Rui-Fen; Li, Yun-Liang; Jiang, Qi-Chuan
Abstract: We proposed a new strategy of combining dynamic freeze casting with pressure infiltration and successfully prepared an antler-bone-inspired gradient metal-ceramic composite. As exemplified by Al-7Si-5Cu/Al2 O3, the resultant composite exhibits the unique mechanical properties of being externally hard, strong, and wear-resistant but internally soft and tough owing to its compositional and structural gradients and delicate lamellar microstructures. This study offers a feasible, flexible, and scalable approach to designing and preparing functionally gradient materials with biomimetic structural features and exceptional properties. Graphical abstract: Unlabelled Image